2021
DOI: 10.1111/sjop.12739
|View full text |Cite
|
Sign up to set email alerts
|

Psychological needs matter more than social and organizational resources in explaining organizational commitment

Abstract: This study investigates the effects of psychological needs satisfaction on teacher’s commitment, over and above the impact of social and organizational resources, by building a model based on the Job Demands‐Resources theory, Self‐Determination Theory, and Conservation of Resources Theory. Hierarchical multiple regressions with data obtained from a sample of 301 Romanian teachers (89% women) reveal that psychological needs satisfaction explains a significant amount of variance in teacher commitment, compared t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 98 publications
0
6
0
Order By: Relevance
“…The explanation of this cognitive pathway can help people realize the importance of organizational commitment. Previous research has shown that superior support creates a positive working environment and exerts a positive effect on subordinates' organizational commitment [ 16 , 97 ]. Since superior trust functions through subordinates' perception of trust [ 5 ], our study bridges a crucial gap by establishing a connection between employees' perceptions of trust from their superiors and their commitment to the organization.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The explanation of this cognitive pathway can help people realize the importance of organizational commitment. Previous research has shown that superior support creates a positive working environment and exerts a positive effect on subordinates' organizational commitment [ 16 , 97 ]. Since superior trust functions through subordinates' perception of trust [ 5 ], our study bridges a crucial gap by establishing a connection between employees' perceptions of trust from their superiors and their commitment to the organization.…”
Section: Discussionmentioning
confidence: 99%
“…Strengthening employees' personal resources may be a fruitful intervention that can reduce burnout [ 79 ] and effectively improve employees work performance [ 80 ]. Simultaneously, research by some scholars, such as [ 16 ]; indicates that personal resources can influence the role played by organizational commitment. Therefore, this study argues that public service motivation as a personal resource closely related to work status, can moderate the relationship between perceived superior trust and organizational commitment.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…When they identify the link between organisational membership on the one hand and time and energy loss, as well as misfit to their psychological needs on the other one, they decrease in organisational commitment (Haider et al, 2020;Stan & Vîrgă, 2021). In the same vein, the overall evaluation of an organisation as politicked is associated with a deteriorated job satisfaction (Agarwal, 2016).…”
Section: Organisational Politics As Reasons For Turnover Intentionmentioning
confidence: 99%
“…in achieving organizational goals (Addink, 2019;Rotberg, 2014;Rothstein, 2012;Sundaram & Chowdhury, 2012). All elements of organizational resources will not function without being handled by humans who are the main movers of the organization (Albrecht et al, 2018;Stan & Vîrgă, 2021;Wicker & Breuer, 2013). Each activity must be timely and acceptable in accordance with the work plan set, or in other words have high effectiveness and performance (Kumar & Gulati, 2010;Mihaiu et al, 2010;Tung et al, 2011).…”
Section: Introductionmentioning
confidence: 99%